Social factors influencing the mega-legacy and mass sport: A case study of the Paris 2024 Olympic Games - Ramazan, Ainur; Salikzhanov, Rinat; Filimonau, Viachaslau (International Journal of Innovative Research and Scientific Studies, 2025)
This study examines the fundamental social factors that influence the mega-legacy, particularly in relation to their long-term impact on mass sport. Utilizing the signals perspective, this research critically reviews both academic and non-academic literature to identify key social factors shaping the mega-legacy and their potential contribution to the expansion and sustainability of mass sports participation. This study aims to quantify perceptions of sports involvement in relation to mass sports development resulting from participation in the Paris 2024 Olympic Games, with 228 respondents participating in the study through a questionnaire. The critical role of sports engagement in shaping expectations and aspirations reinforces previous studies on the significance of legacy in promoting mass sports. Hosting the Olympic Games can be a worthwhile investment if it effectively re-engages sports participation, aligns with the host nation's goals, and supports a long-term sports legacy. This is the first paper considering social factors influencing the legacy in the context of the future development of mass sport, which discusses the key features of mega legacy.